COMPARISON OF SCIENCE LITERACY LEVELS IN STUDENTS’ BIOLOGY TEXTBOOKS IN UNITED KINGDOM, MALAYSIA, AND INDONESIA ON THE TOPIC OF RESPIRATORY SYSTEM - Ujung, Siti Nuraisah Asma (Universitas Negeri Medan, 2024)
This research aims to compare scientific literacy levels in textbooks from three different publishers in three countries. This study is a qualitative approach with a content or document analysis method by describing the level of science literacy of biology textbooks based on aspects of science literacy. Samples were obtained from Indonesia’s textbooks from Erlangga publisher, Malaysia’s textbook from UG Press Sdn, Bhd, and Cambridge publisher. The result shows that the aspect of science as a body of knowledge has the highest average of 67.40% (good), the aspect of science as a way of investigating with the average of 21.31% (deficient), the aspect of science as a way of thinking with the average of 21.31% (deficient), the aspect interaction of science, technology, and society with the average of 6.66% (poor).